2021
DOI: 10.1111/appy.12472
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive mapping review of suicide in vulnerable populations in low and middle countries

Abstract: Introduction In 2016, low‐and‐middle income countries (LMICs) accounted for 79% of the global suicide deaths. In LMICs, vulnerable groups—women, sexual minorities and refugees, and internally displaced persons (IDPs)—are at high risk of suicidal ideation, attempts and deaths by suicide, but information for designing targeted interventions for them is fragmented and missing, making it difficult to address gaps in the existing system. This review highlights these gaps by mapping: (a) risk factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…According to Lester et al, gender inequalities may play a role in higher suicide rates in Africa and family power dynamics and domestic violence may contribute to this [ 41 ]. A narrative synthesis by Vijayakumar et al further suggested that the suicide rate among African refugees was higher [ 42 ]. As Africa is home to the largest number of refugees, suicide among refugees might be an important factor behind the increasing overall rate of suicide deaths in African countries.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lester et al, gender inequalities may play a role in higher suicide rates in Africa and family power dynamics and domestic violence may contribute to this [ 41 ]. A narrative synthesis by Vijayakumar et al further suggested that the suicide rate among African refugees was higher [ 42 ]. As Africa is home to the largest number of refugees, suicide among refugees might be an important factor behind the increasing overall rate of suicide deaths in African countries.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, due to lockdown and school closures during the COVID-19 pandemic in early 2020 [ 8 10 ], prevalence estimates of depression and anxiety were 57.0% and 36.7%, respectively, among adolescents in China [ 10 ]. Depression and anxiety account for 16% of the global burden of disease for adolescents worldwide [ 1 , 11 , 12 ] and are among the major contributing factors for disability, substance use, self-harm, and suicide behaviors among adolescents [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because self‐poisoning is the leading cause of poison exposure in Thailand, 8 identifying the unique characteristics of patients is necessary to develop a tailor‐made multidimensional approach and suicidal prevention program in specific areas. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%